Insulin Resistance, Central Obesity and Risk of Colorectal Adenomas - Ortiz, Ana Patricia (2011)
BACKGROUND: Increasing evidence supports insulin resistance (IR) as the underpinning of the obesity-colorectal neoplasia link. The homeostasis model assessment-IR (HOMA-IR) is a widely accepted index of evolving hyperinsulinemia and early IR. Studies of the relationship between HOMA-IR and colorectal adenomas are limited. Therefore, we sought to determine the associations of HOMA-IR and central obesity [waist-to-hip ratio (WHR)] with risk of colorectal adenomas in a screening colonoscopy-based study. METHODS: We have collected lifestyle information and fasting blood samples from 1,222 participants (320 incident adenoma cases and 902 without adenomas) prior to their screening colonoscopies. Unconditional logistic regression models were used to assess risk associations. RESULTS: In multivariate analysis of participants (n=1,093) reporting no anti-diabetic medication use, those in the top quartile of WHR were twice as likely (OR = 2.18, 95% CI = 1.33 – 3.57, p-trend = 0.003), and those in the top quartile of HOMA-IR were 63% more likely (OR = 1.63, 95% CI = 1.09 – 2.44, p-trend = 0.01), to have adenomas compared to those in the bottom quartiles. Stratified analysis revealed a statistically significant interaction between HOMA-IR and gender (p-interaction = 0.04) with the association largely limited to men: compared to those in the bottom tertile, men in the top tertile of HOMA-IR were twice more likely to have adenomas (OR = 2.11, 95% CI=1.18–3.78, p-trend=0.01). CONCLUSIONS: Our results support central obesity and insulin resistance, particularly in men, as important risk factors for the development of early colorectal neoplasia.